Primary hemostatic function in dogs with acute kidney injury. (5th August 2019) - McBride, Duana; Jepson, Rosanne E.; Cortellini, Stefano; Chan, Daniel L.
Abstract: Background: Bleeding tendencies can occur with uremia. Objectives: To characterize primary hemostatic function in dogs with acute kidney injury (AKI). Animals: Ten dogs with International Renal Interest Society AKI grade III or above and 10 healthy controls. Methods: Prospective study comparing PCV, platelet count, platelet aggregometry (Multiplate), and von Willebrand factor antigen to collagen binding activity ratio (vWF:Ag:vWF:CBA) in 2 groups of dogs (AKI group versus controls). Buccal mucosal bleeding time was measured in the AKI group only. Data are presented as median [25th, 75th percentile] unless otherwise stated. Significance was set at P < .05. Results: Mean PCV was significantly lower in the AKI (34.7%; ±SD, 8.8) than in the control (46.1%; ±SD, 3.6; P < .001) group. Platelet count was significantly higher in the AKI (350.5 × 10 3 /μL [301, 516]) than in the control (241 × 10 3 /μL [227, 251]; P = .01) group. Collagen‐activated platelet aggregometry measured as area under the curve was significantly lower in the AKI (36.9 ± 17.7) than in the control (54.9 ± 11.2; P = .05) group. vWF:Ag:vWF:CBA was significantly higher in the AKI (2.2 [1.9, 2.6]) than in the control (1.1 [1.1, 1.2]; P = .01) group. There was a strong correlation between vWF:Ag:vWF:CBA and creatinine ( r = 0.859; P < .001), but no other variables. Conclusions and Clinical Importance: Dogs with AKI had decreased collagen‐activated platelet aggregation and appear to have a type II von Willebrand disease‐like phenotype as indicated by the high vWF:Ag:vWF:CBA.